THE KNOWLEDGE OF ELEMENTARY CHILDREN ABOUT SEX IN THE SDN CANDIMULYO 1 DISTRICT OF JOMBANG REGENCY JOMBANG - . Juwitasari; Asrina Pitayanti; Bambang Tutuko (Jurnal Keperawatan, 2015)
Sex is already up in emergency situations that should get special handling from various partiesespecially religious figures, education activity and government whoearnthe trustofthe peoplefor thewelfareandhappinessof life of thenation. The incidence of children lack knowledge about sex in 2009due to lack of information. The purpose of this research was to analyze the effect of counseling aboutearly knowledge of sex to the elementary children in the SDN Candimulyo 1 Jombang.This researchdesign was pre-experimental. This research experiment was conducted on March until July 2015.Location of the research was in the SDN Candimulyo 1 district of Jombang, Jombang regency. Theindependent variable in this research was counseling of sex to the elementary children. The sampletaking used by simple random sampling method with the sample was 32 children.The research resultobtained there was increasing knowledge of sex before being conducted counseling were 19 children(59%) and after being conducted counseling occurred increasing knowledge of sex was amounted 37children (84%), while from the result of wilcoxon test obtained result 0,008, so H1 accepted and H0rejected.The conclusion of this research was there’s the effect between the counseling against knowledge of sexto the elementary student in the SDN Candimulyo 1 Jombang, in respect of there was still lack ofknowledge about a good behavior meant boys and girls in terms of dressing can be applied well inaccordance with the teachings of Islam and it started earlyKey words : knowledge of sex, sex